Immunobiology of Varicella-Zoster Virus Infection. (22nd September 2018) - Laing, Kerry J; Ouwendijk, Werner J D; Koelle, David M; Verjans, Georges M G M
Abstract: Varicella-zoster virus (VZV) causes clinically significant illness during acute and recurrent infection accompanied by robust innate and acquired immune responses. Innate immune cells in skin and ganglion secrete type I interferon (IFN-I) and proinflammatory cytokines to control VZV. Varicella-zoster virus subverts pattern recognition receptor sensing to modulate antigen presentation and IFN-I production. During primary infection, VZV hijacks T cells to disseminate to the skin and establishes latency in ganglia. Durable T- and B-cell memory formed within a few weeks of infection is boosted by reactivation or re-exposure. Antigen-specific T cells are recruited and potentially retained in VZV-infected skin to counteract reactivation. In latently VZV-infected ganglia, however, virus-specific T cells have not been recovered, suggesting that local innate immune responses control VZV latency. Antibodies prevent primary VZV infection, whereas T cells are fundamental to resolving disease, limiting severity, and preventing reactivation. In this study, we review current knowledge on the interactions between VZV and the human immune system.